The influence of forest ecosystems on the well-being of surrounding communities: A philosophical perspective in eschatology through guattari’s three ecologies - Syarafina, Aflah Fildzah; Ilmi, Aisyah Nurul; Valencia, Chelsea Indri; Setiyawati, Eka Kurnia; Rasyid, Muhammad Reza Al; Maulida, Nada Azka; Ramadhan, Siti Shalu; Herrnsdorf, Yahsya Naura Azka (Life and Death: Journal of Eschatology, 2025)
Background: This paper examines the influence of UI Forest on the well-being of surrounding communities through Felix Guattari’s Three Ecologies perspective. The research addresses how the presence of UI Forest as an urban green space affects the physical and mental well-being of nearby residents, particularly amid the techno-scientific transformation era that threatens ecological balance. Methods: The study employs Guattari’s Three Ecologies theory, which views ecology through three dimensions: mental, social, and environmental. Data was collected through in-depth interviews with 15 respondents, including local residents and UI Forest users, such as cycling communities and runners. Findings: The analysis utilizes Guattari’s ecosophical approach, which integrates ethico-political and aesthetic aspects in understanding human-environment relationships. The findings reveal that UI Forest plays a significant role in enhancing community well-being by providing space for physical activities, contemplation, and social interaction. Access restriction policies hinder UI Forest’s potential in supporting community welfare. Conclusion: A country's happiness index is very important. The happiness index value is a consideration for policy makers in making regulations and implementing national programs. Novelty/Originality of this article: The novelty of this study lies in the multidimensional approach in analyzing the happiness index in Indonesia by considering factors that have rarely been comprehensively studied in previous studies.